A facile strategy for the synthesis of branched Pt–Pd–M (M = Co, Ni) trimetallic nanocrystals. Issue 22 (21st January 2016) - Mao, Junjie; Pei, Jiajing; Peng, Qing; Wang, Dingsheng; Li, Yadong
Abstract : Pt-based branched nanocrystals (NCs) have attracted much attention because of their unique properties. Abstract : Pt-based branched nanocrystals (NCs) have attracted much attention because of their unique properties. In this work, we employed a facile and efficient route to synthesize highly branched Pt–Pd–M (M = Co, Ni) trimetallic NCs via a one-pot strategy in an octadecylamine (ODA) system. The formation process and influencing factors of the reaction were discussed based on the experimental observations. Further electrochemical measurements indicated that the branched NCs showed enhanced catalytic activities.